A sensitive and stable acetylcholinesterase biosensor with TiO2 nanoparticles anchored on graphitic carbon nanofibers for determination of organophosphate pesticides. Issue 24 (6th June 2022) - Tao, Shihan; Guo, Yuan; Wang, Shuqin; Xu, Fangting; Zhou, Xiaoping; Guo, Qiaohui
Abstract : Electrode materials play a central role in assembling biosensors. Abstract : Electrode materials play a central role in assembling biosensors. In this work, a titanium dioxide nanoparticle loaded graphitized carbon nanofiber (TiO2 /GNF) composite is prepared for the sensitive detection of organophosphorus pesticide residues (OPs). The TiO2 /GNF composite with superior conductivity, catalytic activity and biocompatibility offers an extremely hydrophilic surface for the effective immobilization of acetylcholinesterase (AChE). Furthermore, the Ti atoms of TiO2 /GNFs could coordinate with AChE to improve its stability, and TiO2 has a strong adsorption on OPs. The developed AChE/TiO2 /GNFs/GCE biosensor showed a high affinity to acetylthiocholine chloride (ATCh) and could catalyze the hydrolysis of ATCh with an apparent Michaelis–Menten constant ( K m ) of 50 μM. The constructed AChE/TiO2 /GNFs/GCE biosensor exhibits a wide detection linear range (1.0 × 10 −13 M to 1.0 × 10 −8 M) with a low detection limit (3.3 fM) for paraoxon determination (a model of OPs). In addition, the developed biosensor possesses remarkable anti-interference, acceptable reproducibility and good long-term stability, and is successfully used for the determination of OPs in lake water, providing a new strategy for the analysis of OPs in ecological environments.